Joint effects of three plant protection products to the terrestrial isopod Porcellionides pruinosus and the collembolan Folsomia candida - Santos, Miguel J. G.
The effects of simultaneous application of plant protection products are of concern since the uses of different products pose an additional risk to non-target soil organisms. The effects of binary combinations of dimethoate, glyphosate and spirodiclofen, an insecticide an herbicide and an acaricide, on the avoidance behaviour of the terrestrial isopod Porcellionides pruinosus and the reproductive effort of Folsomia candida were assessed using the two reference models of concentration addition (CA) and independent action (IA). Results of single exposure to the three pesticides indicated a clear dose related avoidance response of the isopods in the highest concentrations tested of the three as well as a strong decrease in collembolan adult survival and concomitant number of juveniles produced. In the combined experiments, antagonism was found in 7 out of the 12 combinations, four combinations followed the reference models, and only in one combination synergism was detected (lower doses of glyphosate and spirodiclofen applied to P. pruinosus). In conclusion, it seems that mixing and applying these products, at the recommended field application rate, does not lead to enhanced toxicity, hence limited risk is associated with the joint application of these pesticides. (C) 2010 Elsevier Ltd. All rights reserved.